1972
DOI: 10.1084/jem.135.3.711
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Interaction in the Immune Response

Abstract: The helper function of carrier-primed T cells was found to be radiosensitive in vivo. The results could not be attributed to interference with the spleen-seeking properties of the irradiated cells. It is suggested that T cell division is essential for the induction of 7S antibody responses in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In contradistinction with B cells, considerable controversy exists with re spect to the radiosensitivity of T cells, especially helper T cells (Anderson et al, 1972Janeway, 1975;Miller and Mitchell, 1968;Claman and Chaperon, general, unprimed T cells are radiosensitive when assayed in vivo or in vitro. Primed T cells, on the other hand, tend to be radiosensitive when assayed in an adoptive transfer system but resistant when assayed in vitro or irradiated in situ.…”
Section: Immunoglobulin In Vivomentioning
confidence: 99%
“…In contradistinction with B cells, considerable controversy exists with re spect to the radiosensitivity of T cells, especially helper T cells (Anderson et al, 1972Janeway, 1975;Miller and Mitchell, 1968;Claman and Chaperon, general, unprimed T cells are radiosensitive when assayed in vivo or in vitro. Primed T cells, on the other hand, tend to be radiosensitive when assayed in an adoptive transfer system but resistant when assayed in vitro or irradiated in situ.…”
Section: Immunoglobulin In Vivomentioning
confidence: 99%
“…Helper T cells in mice have been found radioresis tant in some studies [17,18], whereas others have found helper effects to be radiosensitive [19,20], In part, these discrepancies relate to whether the assay is carried out in vivo or in vitro, but the functional state of the irradiated cells appears to be equally impor tant. Helper cells leaving primed peripheral lymph nodes of mice have never been looked at and we see no controversy in the finding that helper cells leaving lymph nodes of sheep synthesize DNA and possibly proliferate elsewhere.…”
Section: Discussionmentioning
confidence: 98%